EFFECTIVE STRATEGIES FOR DEVELOPING SPEAKING SKILLS IN SECOND LANGUAGE LEARNING - Shaymardonova Farangiz; Tursunova Munira (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores effective methods and strategies for developing speaking skills in second language acquisition. Speaking is considered one of the most important yet challenging skills for language learners. The study highlights the importance of communicative competence, interactive activities, and learner-centered approaches. Both theoretical and practical aspects of teaching speaking are discussed, including the role of motivation, classroom environment, and teacher support. The findings suggest that consistent practice, real-life communication tasks, and feedback significantly improve learners’ speaking abilities.